Effectiveness of Labor Dance on Duration of the First Active Phase of Labor in Nulliparous Women - Meta, Raharni Rosfiyanti; Sumarni, Sri; Suharsono, Suharsono (Sarana Ilmu Indonesia (salnesia), 2024)
Prolonged labor, also known as failure to progress, occurs when the total duration of labor is more than 24 hours and if not handled properly will cause various complications for the mother and baby and even lead to death. This study aimed to determine the effectiveness of labor dance on the duration of the first active phase of labor in nulliparous women. This study was a true experimental randomized controlled trial (single blind) with a posttest only with control group design. This research was conducted from 1 February to 31 March 2023 at the Central General Hospital Prof. dr.I.G.N.G Ngoerah Denpasar and Regional General Hospital Wangaya Denpasar. 42 primigravida mothers were randomly selected according to arrival, with 21 people in the intervention and control groups. Data were analyzed using the Mann Whitney test. The average length of the first stage of labor in the experimental group was 252,62 minutes and in the control group was 355,95 minutes (p-value=0,000); effect size of 1,61 (strong effect) with a percentage of 94,5%. There was a statistically significant difference in the duration of the active phase I stage of labor between the experimental and control groups. It is hoped that health workers, especially midwives, will